Graded Events: What does a grade mean? Considerations on grading for students, teachers, and families. - Grier, Jeanne (Allies for Education, 2019)
The purpose of this presentation is to present a platform that promotes equitable grading practices. The legal implications for grading is first introduced to provide the justification for grading practices that do not impinge of the liberty of students. Topics of late work, due dates, homework, grade inflation, and confidentiality are addressed through equitable lenses.